NUTRIENT CONCENTRATIONS IN THREE NEPENTHES SPECIES (NEPENTHACEAE) FROM NORTH SUMATRA - Muhammad Mansur; Andi Salamah; Edi Mirtanto; Francis Q Brearly (Reinwardtia, 2022)
MANSUR, M., SALAMAH, A., MIRMANTO, E. & BREARLEY, F. Q. 2022. Nutrient concentrations in three Nepenthes species (Nepenthaceae) from North Sumatra. Reinwardtia 21(2): 55‒62. — Nepenthes is a genus of carnivorous plants that are unique ornamental plants, but their nutrient concentration relationships have not been studied much, especially in endemic species on the island of Sumatra. So far, the analysis of the nutrient concentration in Nepenthes is mostly limited to leaves. There are few reports of nutrient concentrations in the pitcher fluid and the soil around where it grows. Leaves, pitcher fluid, and soil around the growth sites of each species i.e., Nepenthes sumatrana, N. spectabilis, and N. tobaica, from North Sumatra province were collected for nutrient analyses (N, P, K, Ca, Mg, and Na). The results showed that the nutrient concentrations in the leaves and pitcher fluid in the three Nepenthes species were generally low with those in the leaves greater than in the pitcher fluid. The concentration of nutrients in the leaves of N. sumatrana (lowland species) was least (except for N and Na) when compared to N. spectabilis and N. tobaica (highland species), likely reflecting the poorly fertile soil. In contrast, the nutrient concentration in the pitcher fluid of N. sumatrana was greater than N. spectabilis and N. tobaica. When compared across an extensive data set, we show that leaf N does not change with elevation, whereas P declines and the N:P ratio increases with elevation, suggesting that Nepenthes plants are obtaining sufficient N from prey at higher elevations.